Oxidized Low-Density Lipoprotein Induces WNT5A Signaling Activation in THP-1 Derived Macrophages and a Human Aortic Vascular Smooth Muscle Cell Line - Ackers, Ian; Szymanski, Candice; Silver, Mitchell J.; Malgor, Ramiro (Frontiers in Cardiovascular Medicine, 2020)
The pathogenesis of atherosclerosis is complex, evolves, and involves many cell types. Macrophages and vascular smooth muscle cells (VSMCs) are critically involved in atherosclerosis development and progression. Several studies have shown that WNT5A protein is abundantly expressed in human atherosclerotic lesions; however, the mechanism and role of WNT signaling pathway activation is not clearly known. Using THP-1 derived macrophages, and human aortic VSMC cells, we evaluated in vitro how oxidized low-density lipoprotein (oxLDL) and WNT5A signaling interact in these two cell lines. We used western blot, scratch assay, metabolic proliferation assay, as well as immunostaining to analyze the effect of Wnt signaling activation. The results demonstrated that oxLDL, as well as WNT5A (control), induced Dishevelled-2 (DVL2) activation and Kif26b degradation, indicating activation of non-canonical Wnt signaling. We found that oxLDL and WNT5A induced FZD5-ROR2 co-localization at the cellular membrane in vitro in THP-1 derived macrophages. Box5 (FZD5 receptor antagonist) inhibited oxLDL-induced DVL2/JNK activation secondary to newly secreted WNT protein from THP-1 derived macrophages. We found that WNT3A (canonical Wnt) and WNT5A showed different roles in this VSMC cell line. These findings indicate that WNT5A is upregulated by oxLDL, promotes foam cell formation, and affects VSMC phenotype and migration in these two cell lines. Also, in these cell lines FZD5 signaling seems to be necessary for lipid accumulation and, through this mechanism, WNT5A could modulate foam cell formation. Thus, our results suggest that WNT5A may contribute to the pathogenesis of vascular disease through modulating macrophage and VSMC behavior.